1988
DOI: 10.1007/bf01963069
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of selective agars and filtration techniques for isolation ofCampylobacter species from faeces

Abstract: Four different studies were conducted in order to re-evaluate conventional methods and assess the efficacy of new selective agars and a filtration method for the isolation of campylobacters. Skirrow's medium, Preston agar, modified CCD agar and Fennell's medium, incubated microaerobically at 37 degrees C for 48 h, gave similar Campylobacter isolation rates from 225 faecal samples, but the latter two media were more selective. Evaluation of modified CCD agar demonstrated that campylobacters could be isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
2
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 17 publications
3
36
2
3
Order By: Relevance
“…In addition, the water samples collected from two different beaches showed a similar trend of significantly higher recovery of campylobacters at 37°C than at 42°C. Similar results were reported by Bolton et al (46), where the majority of campylobacters showed better recovery and culturability at 37°C than at 42°C.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the water samples collected from two different beaches showed a similar trend of significantly higher recovery of campylobacters at 37°C than at 42°C. Similar results were reported by Bolton et al (46), where the majority of campylobacters showed better recovery and culturability at 37°C than at 42°C.…”
Section: Discussionsupporting
confidence: 90%
“…jejuni. Conversely, Bolton et al (46) showed that C. fetus subsp. fetus grew better at 37°C than at 42°C.…”
Section: Discussionmentioning
confidence: 97%
“…Faecal samples were examined for Campylobacter species by culture on modified charcoal cefoperazone deoxycholate agar (CCDA ; Oxoid) and by the membrane filter method (Bolton et al, 1988 ;Steele & McDermott, 1984 Campylobacter hominis sp. nov.…”
Section: Methodsmentioning
confidence: 99%
“…Atypical Campylobacter spp. from stools are dif®cult to culture on the selective media that are used for C. jejuni and C. coli [3,4] and multiple techniques have been combined to improve the isolation rate of species other than C. jejuni and C. coli [13,15,16]. The combined use of selective and nonselective media with a ®ltration technique has been shown to improve isolation rates [9,17].…”
Section: Resultsmentioning
confidence: 99%